Meningkatkan Hasil Belajar Akuntansi Melalui Model Team Games Tournament dengan Motivasi Sebagai Variabel Moderator - Ilah Ilah; Rini Agustin Eka Yanti; Yuyun Susanti; Endang Mulyadi (Universitas Galuh, 2023)
This study describes the use of the Team Games Tournament learning model with moderator variables of student learning motivation in accounting economics subjects. The purpose of this study was to evaluate differences in student learning outcomes using the Team Games Tournament Learning Model and conventional methods, including these differences in students with high and low motivation, as well as analyze the interaction between learning models, motivation, and student learning outcomes in economics subjects at Public High School 3 Kota Banjar. The method used in this study is the Quasi-Experimental method. The design used is a factorial experiment design. Data collection techniques are carried out using test and observation methods. The subject of the study was a grade XI student of the Department of Social Sciences, State High School 3 Banjar City. The results of the study 1) the Team Games Tournament learning model is more effective than learning using conventional methods; 2) there is no significant difference between the learning outcomes of students who have high motivation both in experimental and control classes with the learning outcomes of students who have low motivation in Economics lessons; 3) There is no significant interaction between learning methods, motivation, and student learning outcomes.